Unveiling the Reaction Mechanism of the Das/Chechik/Marek Synthesis of Stereodefined Quaternary Carbon Centers - Pedro J. Silva; Carlos E. P. Bernardo (Applied Sciences, 2021)
The reaction mechanism of the Cu+-catalyzed introduction of two all-carbon-substituted stereocenters in an ynamide system using a Grignard reagent, a zinc carbenoid, and an aldehyde, was investigated using density-functional theory. In contrast to the formation of an organocopper(I) compound and subsequent carbocupration reaction, previously postulated as the initial step, the reaction proved to instead proceed through an initial complexation of the substrate alkyne bond by the Cu+-catalyst, which primes this bond for reaction with the Grignard reagent. Subsequent addition of the zinc carbenoid then enables the nucleophilic attack on the incoming aldehyde, which is revealed as the rate-limiting step. Our computations have also identified the factors governing the regio- and setereoselectivity of this interesting reaction, and suggest possible paths for its further development.